Periodic Coulomb dynamics of three equal negative charges in the field of six equal positive charges fixed in octahedron vertices - Skrypnik, W. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 517.9 We find periodic solutions of the Coulomb equations of motion for three equal negative point charges in the field of six equal positive point charges fixed at the vertices of a octahedron. The system possesses an equilibrium configuration. The center Lyapunov theorem is applied.